Role of Proton Beam Therapy in Hepatic Oligometastasis: Review of Evidence - Rath, Satyajeet (Acta medica Lituanica, 2025)
Hepatic oligometastasis (hOMC) incidence varies from 10-40% in the literature. While the old standard for local treatment was surgical resection, options like TACE, TARE, SBRT with photons and off late protons have come to the fore. The proton beam therapy (PBT) use has gradually started to get adopted in all regions worldwide with increasingly better availability and ever-reducing costs. The role of PBT in hOMC has been studied in many retrospective cohort studies. Although there is a plethora of evidence on photon-SBRT, there are very few analyses on the role of PBT in hOMC. The author intends to analyse the efficacy in terms of the local control (LC) and the overall survival (OS) for PBT and its toxicity profile in this systematic review. LC remains persistently high (76–89% at 1–2 years) across breast, colo-rectum, stomach, and esophagus. Sites like colo-rectum and breast show relatively better survival outcomes, with progression free survival (35–52% at 1–2 years) and OS (33–78% at 1–2 years) than other sites, likely due to disease biology. Breast primary derived hOMCs had the best 3-year OS of 67.6%. Toxicities remain remarkably low with grade 3 plus toxicities ranging from 0–3%, which reflects the ability of proton therapy to deliver beams with precision.
Keywords: oligometastatic cancers; Proton beam therapy; hepatic oligometastasis; liver secondary; toxicity profile